A simple approach for sensing and accurate prediction of multiple organic vapors by sensors based on CuO nanowires - Kulkarni, Saraswati; Ghosh, Ruma (Sensors and actuators. B, Chemical, 2021)
•CuO nanowires have been synthesized using a facile solution phase method.•The room-temperature operability of CuO sensors were developed for methanol, acetone and acetonitrile and might aid in reducing the power requirements of the sensors.•A simple algorithm was developed in this research that could predict the vapors fairly accurately.•The prediction accuracy of the algorithm was improved when high-temperature data was included with room temperature data.•This work includes integration and application of knowledge of different domains to aid in prototype and product development. Development of sensors that can sense volatile organic compounds (VOCs) efficiently is imperative for different real-life applications. This paper reports synthesis of CuO nanowires using a facile solution-phase technique. The samples were found to have monoclinic polycrystalline structure when characterized using an X-ray diffractometer (XRD). The morphology was confirmed to be nanowires with diameter of approximately 10 nm when studied using field emission scanning electron microscope (FESEM), and the bandgap of the CuO nanowires was found to be 1.9 eV when characterized using UV–vis spectroscopy. The CuO nanowires based sensors were tested for five different concentrations (500–7000 ppm) of methanol, acetone, and acetonitrile at room temperature (25 °C) and four different concentrations (500–5000 ppm) of the three vapors at 200 °C. At room temperature, the response of the sensor ranged between 4.3 % and 29.9 %, 0.83 % and 14.7 %, and 1 % and 7 % for 500–7000 ppm methanol, acetonitrile, and acetone respectively. The response of the sensor was observed to be ranging between 13 % and 70 %, 150 % and 700 %, and 610 % and 2300 % for 500–5000 ppm of methanol, acetonitrile, and acetone respectively when tested at 200 °C. A novel and simple algorithm was developed that considered the initial 60 s responses of CuO nanowires exhibited for methanol, acetone, and acetonitrile at room temperature and at 200 °C and could predict the vapors along with their concentrations accurately.